Editing the Nepalese Journal of Ophthalmology: a voyage of five years - Badhu, B; Kadel, T (Nepalese Journal of Ophthalmology, 2013)
Nepal J Ophthalmol 2013; 5(10): 143-144 DOI: http://dx.doi.org/10.3126/nepjoph.v5i2.8703